Breastfeeding: science and knowledge in pediatric obesity prevention - Muraglia, Marilena; Faienza, Maria Felicia; Tardugno, Roberta; Clodoveo, Maria Lisa; Matias De la Cruz, Carmen; Bermúdez, Fátima German; Munizaga, María Gabriela; Valencia, Luz; Corbo, Filomena; Orellana-Manzano, Andrea (Frontiers in Medicine, 2024)
The increasing prevalence of childhood obesity worldwide is a significant concern due to its link to severe health issues in adulthood, such as non-communicable diseases (NCDs). To address this issue, this review evaluates the effectiveness of various preventive measures for childhood obesity, focusing on maternal nutrition and breastfeeding. The study underscores the criticality of the periconceptional period, where the diets of both parents can influence epigenetic modifications that impact the child's metabolic pathways and obesity risks. Breastfeeding is a potent protective mechanism against earlyonset obesity, significantly enhancing the infant's metabolic and immune health by modifying DNA methylation and gene expression. Furthermore, the perspective underscores the significance of the Mediterranean diet during the periconceptional period and lactation. This diet can effectively prevent gestational complications and improve breast milk quality, fostering optimal infant development. Recognizing that obesity results from genetic, epigenetic, environmental, and social factors, the paper advocates for a comprehensive, multidisciplinary approach from the earliest stages of life. This approach champions a balanced maternal diet, exclusive breastfeeding, and timely introduction to complementary foods. In conclusion, addressing pediatric obesity requires a multifaceted strategy emphasizing improving prenatal and postnatal nutrition. Further research is necessary to understand the epigenetic mechanisms influenced by nutrition and their long-term effects on children's health. This will help refine interventions that curb the obesity epidemic among future generations.